Advances in Agricultural Machinery and Technologies - Chen, Guangnan; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
The agricultural industry is dealing with enormous challenges across the globe, including the limited availability of arable lands and fresh water, as well as the effect of climate change. Machinery plays a crucial role in agriculture and farming systems, in order to feed the world$1 (Bs growing population. In the last decade, we have witnessed major advances in agricultural machinery and technologies, particularly as manufacturers and researchers develop and apply various novel ways of automation as well as the data and information gathering and analyzing capabilities of their machinery. This book presents the state-of-the-art information on the important innovations in the agricultural and horticultural industry. It reviews and presents different novel technologies and implementation of these technologies to optimize farming processes and food production. There are four sections, each addressing a specific area of development. Section I discusses the recent development of farm machinery and technology. Section II focuses on water and irrigation engineering. Section III covers harvesting and post-harvest technology. Section IV describes computer modelling and simulation. Each section highlights current industry trends and latest research progress. This book is ideal for those working in or are associated with the fields of agriculture, agri-food chain and technology development and promotion.s
Section I: Farm machinery and technology--Mechanisation of agricultural production in developing countries -- Developments in mechanisation technology: controlled traffic farming -- Mechanisation of vegetable production -- Development in energy generation technologies and alternative fuels for agriculture -- Applied machine vision in agriculture -- Advances in unmanned aerial systems and payload technologies for precision agriculture -- Agricultural robotics -- Development of precision livestock farming technologies -- Section II: Water and irrigation engineering-- -- 9. Efficient use of energy in irrigation-- -- -- 10. Advances in surface irrigation technology-- -- -- 11. Advanced tools for irrigation scheduling-- -- --12. Minimising evaporation loss from irrigation storages -- Section III: Harvesting and post-harvest technology -- -- -- 13. Advances in silage harvest operations-- -- -- 14. Drying of agricultural crops-- -- -- 15. The fruit and vegetable packhouse: technologies for assessing fruit quantity and quality -- Section VI:Computer modelling-- -- -- 16. Crop modelling for agricultural machinery design-- -- -- 17. Three-dimensional numerical modelling of morphogenesis in dehydrated fruits and vegetables.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / General; TECHNOLOGY & ENGINEERING / Industrial Design / General; Agricultural machinery; Agricultural innovations; Electronic books